Framework to harvest waste heat from microprocessor using MEMS thermoelectric generator - Ling T.Z.; See O.H. (Maxwell Science Publications, 2023)
The world primary energy consumption has been growing steadily. Therefore, there is a need to improve the overall energy application. There is a lack of investigation on harvesting waste heat from microprocessor as an alternative energy source. This study focuses on the framework required to harvest the energy from the microprocessor. Thermal profiling of the microprocessor integrated with an MEMS Thermoelectric Generator (TEG) using shunt configuration is developed. Additionally, a non-uniform energy model is derived to estimate the amount of energy that can be harvested from the microprocessor in the shunt configuration. MATLAB simulation based on the thermal and energy model is presented with two types of heat spreader material, copper and pyrolytic graphite with ideal and non-ideal contacts. The advantages and their shortfalls with respect to the microprocessor heat dissipation and the effectiveness to generate a temperature gradient at the MEMS TEG are discussed.